Adaptabilidade de híbridos entre Gossypium barbadense E G. hirsutum N contendo o gene cry1Ac - Sousa, Jair Moisés de (2009)
Hybrids among transgenic plants and related species are expected to occur if they are sympatric and when there are not crossing barriers; as is the case, in Brazil, of cry1Ac transgenic cotton and Gossypium barbadense. This species has been maintained as dooryard plants, and should be preserved as a genetic resource. Hybrids were evaluated about traits related to fitness, leading to infer about its chances of survivor and selection. A barbadense genotype collected at the state of Mato Grosso was outcrossed to the variety DP 404, containing the gene cry1Ac, and to the isoline DP 404. All the F1 individuals and 122 among 170 F2 individuals expressed the toxin, and presented levels of resistance to pink bollworm (Pectinophora gossypiella) and cotton leafworm (Alabama argillacea) equivalent to the transgenic parent and superior to the isoline, barbadense or non transgenic hybrids. The percentage of germination and number of days to germinate did not differ among genotypes. Anthesis of the first flower and opening of the first cotton boll occurred earlier for herbaceous cotton and F1 hybrids than F2 population in average; all the populations presented a number of days to flower and opening of the first boll smaller then barbadense. The highest plants were barbadenses, and herbaceus the smallest, with F1 and F2 populations presenting intermediary heights. The number of seeds per plants were superior for F1 hybrids an herbaceous cotton, F2 populations were in average intermediary; the barbadense genotype produced the smallest number of seeds per plant. Pink bollworm, mainly, and also cotton leafworm, are important barbadense pests, so the transgene positive effect could favor the selection of hybrids, and hence G. hirsutum genome, against the maintenance of pure G. barbadense genome. The selection may be influenced by the plant uses: the smaller size of hybrids when compared to the barbadense may lead them to be differentiated from these parents to which medicinal properties are attributed; on the other hand, the greater boll production may favor hybrids maintenance with the purpose of producing lamp wicks, or use as an ornamental or swab